2022
DOI: 10.1038/s41598-022-16174-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of microRNA-30d in pancreatic beta-cells progressively regulates beta-cell function and identity

Abstract: Abnormal microRNA functions are closely associated with pancreatic β-cell loss and dysfunction in type 2 diabetes. Dysregulation of miR-30d has been reported in the individuals with diabetes. To study how miR-30d affects pancreatic β-cell functions, we generated two transgenic mouse lines that specifically overexpressed miR-30d in β-cells at distinct low and high levels. Transgenic overexpressed miR-30d systemically affected β-cell function. Elevated miR-30d at low-level (TgL, 2-fold) had mild effects on signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Instead, we chose to study hsa-mir-30e-3p, a member of the miRNA-30 family, which is highly expressed in beta-cells, according to the same database. Interestingly, members of the miRNA-30 family have been reported to affect beta-cell insulin production, apoptosis and transdifferentiation to alpha-cells, and to function as biomarkers for pre-diabetes (30)(31)(32). We observed that blocking the binding of hsamir-30e-3p to ADA1 mRNA resulted in reduced intracellular adenosine levels, both at control conditions and in cells exposed to palmitate + high glucose (Figure 8A).…”
Section: Sirna-mediated Downregulation Of Ada1 Increases Cell Death I...mentioning
confidence: 85%
“…Instead, we chose to study hsa-mir-30e-3p, a member of the miRNA-30 family, which is highly expressed in beta-cells, according to the same database. Interestingly, members of the miRNA-30 family have been reported to affect beta-cell insulin production, apoptosis and transdifferentiation to alpha-cells, and to function as biomarkers for pre-diabetes (30)(31)(32). We observed that blocking the binding of hsamir-30e-3p to ADA1 mRNA resulted in reduced intracellular adenosine levels, both at control conditions and in cells exposed to palmitate + high glucose (Figure 8A).…”
Section: Sirna-mediated Downregulation Of Ada1 Increases Cell Death I...mentioning
confidence: 85%
“…At the same time though, miR-375 has been found to be dysregulated both in experimental [273,274] and real-life conditions related to T2D [275]. In addition, other malfunctioning miRNAs have been found to play a role in β-cell failure and T2D pathogenesis, such as miR-7, miR-9, miR-29, and miR-30d, among several others [272,276]. No studies have been published so far regarding the possible association between micronutrients and miRNA levels in patients with T2D, but a recent study by Ferrero et al [277] showed a link between habitual diet nutrients and circulating miRNA profiles in healthy subjects.…”
Section: Role Of Mirnas Dysfunctionmentioning
confidence: 99%
“…Its overexpression in beta-cells leads to hyperglycemia, reduced insulin level and glucose intolerance in mice fed HFD. Interestingly, miR-30d negatively affects beta-cells identity by downregulating beta-cell markers and inducing the expression of alpha-cell markers (73).…”
Section: Mirnas As Gatekeepers For Beta-cell Apoptosismentioning
confidence: 99%